Developments in mercury removal from natural Gas-A short review - Abbas, T. (Trans Tech Publications Ltd, 2014)
Almost all hydrocarbons contain mercury up to different levels depending upon the locality and region. In the case of natural gas and natural gas liquids, it is likely to be present as elemental mercury. However in crude oil, it may also be present as organo-metallic and ionic mercury. The presence of mercury in refinery hydrocarbon streams not only results in detrimental effects, including catalyst poisoning, corrosion, safety issues but also anthropogenic increase of mercury level in environment which has provoked the search for environmental friendly techniques to capture the mercury from process streams. In this paper, the available techniques, current limitations and future prospects for mercury removal from natural gas are discussed. Â© 2014 Trans Tech Publications, Switzerland.